(untitled) (Journal of Education and Development, 2022)
This study investigated the relationships of paid and unpaid internships to anticipated employment outcomes for graduating college business students. It also investigated the self-reported source(s) by which these students had obtained their internship(s). In May of 2020, 445 graduating business undergraduates filled out an online survey, for which there was complete data for 405 students. Although most of the internships were pre-pandemic, the anticipated employment outcomes by graduation were in the early stage of the COVID-19 pandemic. Three dichotomous response anticipated employment outcomes were measured: securing a full-time job; securing a full-time job that consistent with one’s major; and being self- employed. Results were that students with at least one paid internship were more likely to anticipate securing a full-time job and securing a full-time job consistent with their major versus students without a paid internship. In addition, students with at least one paid internship were less likely to see themselves being self-employed versus students without a paid internship. However, there were no relationships for students having at least one unpaid internship, versus no unpaid internship, to these anticipated full-time employment outcomes. Students with at least one unpaid internship were more likely to see themselves being self-employed by graduation versus students without an unpaid internship. Surprisingly, the general source of “on my own” was the dominant method reported by students for obtaining both paid and unpaid internships. These results are further discussed, and study limitations noted.